The Effect of Library Facilities and Librarian Performance on The Reading Interest of Students of the Islamic Education Management Study Program, Darussalam Islamic Institute of Religion 2021 Academic Year 2022/2023 - Maulana Akrom; M. Khusna Amal; Khotibul Umam (Cita Konsultindo Research Center, 2023)
One ofthe factors that influence interest in reading is how well the existing facilities and infrastructure, in managing a library that is arranged so beautifully and comfortably in its place. The facilities always develop by following this modern era. Through a quality library an institution or organization can be said to be advanced. The better the quality of the library the more interested ones to visit it. The data collectionmethods used include: observatian, questionaire, interview and documentation. For data validity using Pearson correlation, while looking for data reliability using corrected item-total correlation, then testing the hypothesis using the product moment formula, data analysts use multiple linear regression. The population in this study was MPI semester 2 students in 20 21 while the sample was the entire population made into a sample of 114 students. After analyzing the data, it can be concluded that: librarians' facilities and performance towards reading interest in the library of As Syafa'ah Banyuwangi Islamic Religion Institute in the academic year 20 22/2023 are quite good. There is an influence of 13%.